2016
DOI: 10.1016/j.psychres.2016.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Does body mass index moderate the association between posttraumatic stress disorder symptoms and suicidal ideation in Iraq/Afghanistan veterans?

Abstract: Suicide, PTSD, and obesity co-occur at high rates among returning veterans, yet limited research exists regarding the relationship among these variables. Self-report and diagnostic interview data from a longitudinal study of Iraq and Afghanistan veterans (N = 130) enrolled in VA healthcare examined these inter-relations. As hypothesized, body mass index (BMI) significantly moderated the association between PTSD and suicidal ideation such that the association between PTSD and suicidal ideation was strongest amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…(2014) measured total serum cholesterol among men with PTSD and found that having higher levels of total cholesterol was significantly associated with a decreased likelihood of reporting SI. In another study, body mass index (BMI) was shown to significantly moderate the relation between PTSD symptoms and SI among a sample of Iraq and Afghanistan war veterans such that those with higher BMI were at higher risk for SI, potentially due to high allostatic load and lower engagement in health‐promoting behaviors (Kittel et al., 2016). Finally, Dell'Osso et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2014) measured total serum cholesterol among men with PTSD and found that having higher levels of total cholesterol was significantly associated with a decreased likelihood of reporting SI. In another study, body mass index (BMI) was shown to significantly moderate the relation between PTSD symptoms and SI among a sample of Iraq and Afghanistan war veterans such that those with higher BMI were at higher risk for SI, potentially due to high allostatic load and lower engagement in health‐promoting behaviors (Kittel et al., 2016). Finally, Dell'Osso et al.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Vilibić et al (2014) measured total serum cholesterol among men with PTSD and found that having higher levels of total cholesterol was significantly associated with a decreased likelihood of reporting SI. In another study, body mass index (BMI) was shown to significantly moderate the relation between PTSD symptoms and SI among a sample of Iraq and Afghanistan war veterans such that those with higher BMI were at higher risk for SI, potentially due to high allostatic load and lower engagement in health-promoting behaviors (Kittel et al, 2016). Finally, Dell'Osso et al (2014) investigated rhythmicity (i.e., circadian and seasonal rhythms) and vegetative functions and found that a lifetime history of all subdomains (i.e., rhythmicity, sleep, appetite and weight, sexual function, and physical symptoms) predicted an increased risk of SI, whereas only changes in the appetite/weight subdomain were predictive of SA.…”
Section: Simentioning
confidence: 99%